Voices from Vilcabamba: accounts chronicling the fall of the Inca Empire - Bauer, Brian S., author; Halac-Higashimori, Madeleine, author; Cantarutti, Gabriel E., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
An overview of major events that occurred in the Vilcabamba region of Peru during the final decades of Inca rule and English translations of several major period documents. A new source of important archival and archaeological information examining the fall of the Inca Empire in unprecedented detail.--Provided by publisher.
Vilcabamba and the fall of the Inca (1536-1572) -- Martín Hurtado de Arbieto and the Spanish colonization of Vilcabamba (1572-1589) -- Document 1: Martín de Murúa and the fall of Vilcabamba: an English translation of Murúa's general history of Peru (chapters 70, 72-85) -- Document 2: Baltasar de Ocampo Conejeros and the province of Vilcabamba -- Document 3: Diego Rodríguez de Figueroa's journey into Vilcabamba [1565] -- Document 4: Antonio Baptista de Salazar and the fall of Vilcabamba -- Document 5: The death, interments, and miracles of Fray Diego Ortiz (Vilcabamba, Peru).
Keywords: Incas -- Peru -- Vilcabamba Mountains Region -- History -- 16th century; Incas -- Peru -- Vilcabamba Mountains Region -- History -- 16th century -- Sources; Vilcabamba Mountains Region (Peru) -- Colonization -- History -- 16th century; Vilcabamba Mountains Region (Peru) -- Colonization -- History -- 16th century -- Sources; Peru -- History -- Conquest, 1522-1548; Peru -- History -- 1548-1820; Peru -- History -- Conquest, 1522-1548 -- Sources; Peru -- History -- 1548-1820 -- Sources